Understanding crime: a multidisciplinary approach - Guarino-Ghezzi, Susan; Treviño, A. Javier (LexisNexis, 2005)
A multidisciplined approach to crime -- Sociological perspectives on crime -- Economics and crime -- Psychological perspectives on crime -- Biological perspectives on crime -- Philosophy and crime -- Religious studies and crime -- Toward an interdisciplinary understanding of crime.